The effect of chlorhexidine gluconate mouthrinse on the color stability of different permanent prosthetic resin materials - ABDULAI, Dalndushe; Velioğlu, Neslin; Cengiz, Seda; Köroğlu, Ayşegül; Cengiz, Murat İnanç (Indonesian Dental Association, 2024)
Introduction: Color stability is a crucial aspect in the longevity and aesthetics of dental prosthetics. Understanding how different materials respond to common oral hygiene practices, such as chlorhexidine mouthrinse, is essential for informed clinical decision-making. This research aims to provide valuable knowledge about the potential effects of chlorhexidine gluconate on the color stability of prosthetic resin materials, contributing to a comprehensive understanding of their performance in actual oral care prognoses. Aim: The aim of this in vitro study was to evaluate the effect of mouthrinse on the color stability of two different laboratory-processed resin composite systems, a resin nanoceramic CAD-CAM material and a 3D printed resin material. Material and Methods: Forty-eight specimens were prepared from two different indirect composite systems (SR Adoro, Ivoclar Vivadent and Tescera ATL, Bisco); a resin nano-ceramic (Lava Ultimate, 3M ESPE) and a 3D printed permanent crown material (Permanent Crown, Formlabs). Surfaces were ground using carbide grinding paper (Grids 600, 800, 1000) followed by a 50µm Al2O3 sandblasting. Then universal polishing paste was applied to the surfaces. The color before and after immersion was measured according to Comission Internationale de L'Eclairage (CIED2000) System and ΔL, Δa, Δb, and ΔE values were calculated. All specimens were immersed in the mouthrinse solution for 24h. Changes in colors (ΔE00) was assessed before and after immersion by a digital spectrophotometer (Vita Easyshade, Vita). Data was analyzed with a one-way ANOVA and a Shapiro–Wilk test of normality was performed. Results: After conducting a one-way ANOVA test, it was found that there were no statistically significant difference between the mean values of ΔE00 in the test groups (p=0.105). The chlorhexidine gluconate mouthrinse did not effect the color change of resin materials manufactured by different methods. Conclusion: Within the limitations of the study, the color stability of the tested resin materials in the chlorhexidine gluconate mouthrinse was not affected.